Understanding digital events : Bergson, Whitehead, and the experience of the digital - Kreps, David, 1963- (Abingdon, Oxon : Routledge, 2019)
This book introduces an events-based approach to understanding digital experience. Focusing on the event-ontologies of Bergson and Whitehead's process metaphysics, it explores subjective experience and objective reality as unified 'events' in the form of concrete slabs of existence. Such slabs are temporally defined by a term or period, in which all physical-chemical processes and personal subjective experience are included. Bringing together insights from a range of different specialisms, it urges us to consider a science of nature that includes both physical and non-physical realities and, from this ontological position, draws on philosophy, media, and user experience practice to provide a new account of the technological or virtual world of today. An examination of the manner in which process philosophy may be applied to contemporary digital experience, this volume will appeal to scholars of philosophy, science and technology studies and information systems.
OCLC-licensed vendor bibliographic record.
Keywords: Bergson, Henri, -- 1859-1941.; Whitehead, Alfred North, -- 1861-1947.; Events (Philosophy); Event processing (Computer science); PHILOSOPHY / Metaphysics; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General